2018
DOI: 10.1590/0074-02760180260
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dual-path Platform chromatographic immunoassay (DPP® CVL rapid test) for the serodiagnosis of canine visceral leishmaniasis

Abstract: BACKGROUND Visceral leishmaniasis is a major public health challenge in South America, and dogs are its main urban reservoir. OBJECTIVE Validation of the canine Dual-path Platform immunoassay for canine visceral leishmaniasis (DPP ® CVL) for a sample set composed of 1446 dogs from different Brazilian endemic areas. METHODS A well-defined reference standard by means of parasitological culture, immunohistochemistry, and histopathology was used. Animals were classified as asymptomatic, oligosymptomatic, or sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“… 4 A larger study, using the same reference standard, made subgroup analysis based on the presence of symptoms revealing that TR-DPP for asymptomatic dogs had a sensitivity of 75% (CI95% 42.8 to 94.5) and specificity of 72.9% (CI95% 68.5 to 77.1) compared to sensitivity of 93.8% (CI95% 82.8 to 98.7) and specificity of 56.4% (CI95% 46.2% to 66.3%) in symptomatic dogs. 8 Finally, DAT- Canis showed a sensitivity of 97% in symptomatic dogs, 21 and its performance had not been previously assessed in diagnosing asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 A larger study, using the same reference standard, made subgroup analysis based on the presence of symptoms revealing that TR-DPP for asymptomatic dogs had a sensitivity of 75% (CI95% 42.8 to 94.5) and specificity of 72.9% (CI95% 68.5 to 77.1) compared to sensitivity of 93.8% (CI95% 82.8 to 98.7) and specificity of 56.4% (CI95% 46.2% to 66.3%) in symptomatic dogs. 8 Finally, DAT- Canis showed a sensitivity of 97% in symptomatic dogs, 21 and its performance had not been previously assessed in diagnosing asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies conducted later have evaluated the sensitivity and specificity of these tests. 4 , 5 , 8 , 34 , 35 , 36 , 37 However, the lack of a homogenous reference standard has caused the results of these studies to diverge, as each one has used a different criterion for defining infected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPP CVL test has also been assessed several times since it was introduced and most recently it has been shown that overall it has 86% sensitivity and 94% specificity[14] or 89% sensitivity and 70% specificity[15].…”
Section: Introductionmentioning
confidence: 99%
“…The DPP CVL test has been assessed several times since it was introduced. The most recent assessment showed that it has 75% sensitivity and 73% specificity for asymptomatic dogs and 94% sensitivity and 56% specificity for symptomatic dogs (Figueiredo et al, 2018) suggesting that the DPP test is better for confirming than identifying cases (Grimaldi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%